Negative Emotion Responses to Heavy-Metal and Hip-Hop Music with Positive Lyrics - Susino, Marco; Schubert, Emery (Empirical Musicology Review, 2019)
This research investigated whether negative emotional responses to heavy-metal and hip-hop music could be stereotypes of the music genres. It was hypothesized that heavy-metal and hip-hop music with positive lyrics would be perceived as expressing more negative (negative valence/high arousal) emotions, compared with pop music excerpts with identical lyrics. Participants listened to either two heavy-metal or two hip-hop test stimuli and two pop control stimuli. They then responded by stating what emotion they perceived that the music expressed. Results indicated that heavy-metal and hip-hop stimuli were perceived as expressing more negative emotions than pop stimuli. Lyrics were recognized above chance in both heavy metal and hip hop, suggesting that the negative emotion bias was not a result of misunderstanding the lyrics. The Stereotype Theory of Emotion in Music (STEM) explains the findings in terms of an emotion filter which is activated to simplify emotion perception processing. The conclusions provide a novel way of understanding the cultural and social contribution of emotion in music.